POSITIONING JASHPUR ON THE ECOTOURISM MAP: OPPORTUNITIES AND CHALLENGES IN CHHATTISGARH - Xaxa, Augustin; Tiwari, Anju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ecotourism has become a pivotal tool for sustainable development, balancing conservation with community development. Jashpur District in Chhattisgarh, with its rich natural resources, diverse ecosystems, and vibrant tribal culture, holds immense potential as an ecotourism destination. However, it remains largely untapped. This paper explores how Jashpur can be positioned as a leading ecotourism destination through a comprehensive analysis of its natural and cultural assets, existing challenges, and sustainable strategies for tourism development. The study examines the critical role of community participation, government policies, and private sector engagement in developing Jashpur into a model ecotourism destination that ensures environmental preservation, socio-economic growth, and cultural heritage conservation.